Estimasi Trend Area Terbakar Pada Hutan dan Lahan Berbasis Citra Radar Sentinel-1 di Kabupaten Ogan Komering Ilir, Sumatera Selatan Tahun 2015-2019 - Ramadhan, Dani; Sidiq, Wahid Akhsin Budi Nur (Geo-Image, 2021)
Ogan Komering Ilir (OKI) District is the district that experienced the worst fires in South Sumatra Province. based on hotspot data for 2019 for the period July to November a total of 8,637 points were caused by the ENSO phenomenon due to climate anomalies that caused forest and land fires. The purpose of this study to identify the trend of land and forest fires in the OKI District during 2015, 2017, and 2019 and analyze the impact caused by the forest fires and land in OKI District during 2015, 2017, and 2019. The collection of data by satellite image interpretation, literature study, observation, and documentation. The sampling method is based on research by Projo Danoedoro in 2015 with a total of 194 samples. The data analysis technique used accuracy test analysis and descriptive statistical analysis. These results indicate that in 2015 and 2019 have the same pattern of burned areas, but not in 2017 and the test results indicated the accuracy of the results of image processing Sentinel 1 by 60%. The impact resulting from the existence of land and forest fires is assumed there are changes in land cover. The results of Landsat 8 processing show that the pattern of significant land cover changes occurs in vegetation, open land, and air cover which are affected by the occurrence of forest and forestry forests based on the 2015, 2017, and 2019 time series. Kabupaten Ogan Komering Ilir (OKI) menjadi kabupaten yang mengalami kebakaran terparah di Provinsi Sumatera Selatan. Berdasarkan data hotspot tahun 2019 periode bulan juli hingga november sejumlah 8.637 titik yang disebabkan oleh fenomena ENSO akibat dari anomali iklim yang memicu terjadinya kebakaran hutan dan lahan. Tujuan dari penelitian ini untuk Mengidentifikasi trend kebakaran hutan dan lahan di wilayah Kabupaten OKI selama tahun 2015,2017, dan 2019 dan menganalisis dampak yang ditimbulkan akibat kebakaran hutan dan lahan di wilayah Kabupaten OKIr selama tahun 2015, 2017, dan 2019. Pengumpulan data dengan intepretasi citra satelit, studi pustaka, observasi, dan dokumentasi. Metode pengambilan sampel berdasarkan penelitian Projo Danoedoro tahun 2015 dengan total 194 sampel. Teknik analisis data menggunakan analisis uji akurasi dan analisis statistik deskriptif. Hasil penelitian ini menunjukan bahwa pada tahun 2015 dan 2019 memiliki kesamaan pola area terbakar namun tidak dengan tahun 2017 dan hasil uji akurasi yang ditunjukan dari hasil pengolahan citra Sentinel 1 sebesar 60%. Dampak yang diakibatkan dari adanya kebakaran hutan dan lahan adalah diasumsikan terdapat perubahan penutup lahan. Hasil dari pengolahan Landsat 8 menunjukan bahwa pola perubahan penutup lahan signifikan terjadi pada penutup lahan vegetasi, lahan terbuka, dan terbangung yang dipengaruhi akibat terjadinya KARHUTLA berdasarkan time series tahun 2015, 2017, dan 2019.